Christianity and developmental psychopathology : foundations and approaches - Flanagan, Kelly S., 1977-; Hall, Sarah E., 1981-; Christian Association for Psychological Studies (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2014)
Since its origin in the early 1980s, the field of developmental psychopathology has become a highly influential framework for approaching the clinical treatment of children. Until now there has been no effort to integrate this framework with a Christian understanding of psychopathology. The essays in this volume provide Christian mental health professionals with a theoretically and empirically sound basis for working with children, adolescents and families. Throughout the book, the authors explore three integrative themes, looking at children as divine gifts, as persons and as agents in their own development. --From publisher's description.
Introduction / Kelly S. Flanagan and Sarah E. Hall -- Overview of developmental psychopathology and integrative themes / Kelly S. Flanagan and Sarah E. Hall -- Section 1: Intrapersonal influences -- Temperament / Amy Mezulis, Kaitlin A. Harding and Melissa R. Hudson -- Emotion regulation / Sarah E. Hall -- Section II: Interpersonal influences -- The parent-child relationship / Winston Seegobin -- The marital and parental dyad / Mari L. Clements, Tara A. Guarino and Laura C. Bartos -- Peer relationships / Kelly S. Flanagan, Sarah L. Kelly and Amy Peeler -- Section III: Treatment and prevention -- Prevention and the promotion of thriving / Pamela Ebstyne King and Casey Erin Clardy -- Intervention : applying a developmental psychopathology framework / Sally Schwer Canning, Kelly S. Flanagan, Jennifer Hailey and Emely de la O -- Section IV: Application from theoretical orientations -- Psychodynamic and attachment-based approaches to treatment / Jana D. Pressley and Kristin K. Vanden Hoek -- Behavioral approaches to treatment / Amanda M. Blackburn, Christine Weisgerber and Michelle Shelley -- Cognitive-behavioral approaches to treatment / Donald F. Walker, Katherine J. Partridge, Anastasia Whitesell, Brittany Montes and Sarah E. Hall -- Family systems approaches to treatment / Sandra Y. Rueger and David van Dyke -- Appendix A: Case formulation worksheet -- Appendix B: Developmental trajectory map -- Appendix C: Select examples of evidence-based treatments.
Includes bibliographical references (pages 399-475) and index.
Keywords: Child psychopathology; Psychotherapy -- Religious aspects; Child psychopathology; Psychotherapy -- Religious aspects